Effects of Growing-Season Prescribed Burning on Vigor of Sericea Lespedeza in the Kansas Flint Hills: I. Suppression of Seed Production and Canopy Dominance - J. A. Alexander; W. H. Fick; J. Lemmon; G. A. Gatson; G. W. Preedy; K C Olson (Kansas Agricultural Experiment Station Research Reports, 2017)
Sericea lespedeza (Lespedeza cuneata) is a highly fecund noxious weed in Kansas and surrounding states. Individual plants are capable of producing greater than 1,000 seeds annually. Vigorous seed production allows sericea lespedeza to rapidly infiltrate native and cultivated grasslands; seed can be transported great distances via farm machinery and the alimentary canal of wild and domestic herbivores. In Kansas alone, sericea lespedeza infests more than 700 square miles of pasture, primarily in the Flint Hills region. The resulting damage to native habitats for wildlife and pasture quality for domestic herbivores has been devastating. The predominant grazing management practice in the Kansas Flint Hills involves annual spring burning in April followed by intensive grazing with yearling beef cattle for a relatively short period from late April to August. During seasonal grazing, 40 to 60% of annual graminoid production is removed and grazing lands then remain idle for the remainder of the year. Under this prevailing management practice, invasion by sericea lespedeza into the tallgrass prairie biome has steadily increased. Oklahoma State University researchers speculated that dormant-season, spring fires may stimulate sericea lespedeza seed germination by scarifying seeds cast the previous fall. Previous research reported that application of growing season fire at 3 year intervals decreased the rate of sericea lespedeza invasion. Therefore, the objective of our study was to evaluate the effects of annual prescribed burning applied during the growing season on vigor of sericea lespedeza infesting native tallgrass range.
Keywords: sericea lespedeza; prescribed burning; growing season